A new species of Pangaeus (Hemiptera: Heteroptera: Cydnidae: Cydninae), with new records of the genus for Mexico - María Cristina Mayorga-Martínez; Alfredo Mayorga (Revista Mexicana de Biodiversidad)
A new species of Pangaeus Stål (Hemiptera: Cydnidae) from Chiapas: P. (Pangaeus) cervantesi sp. nov., is described and illustrated. New records for Mexico for the following species are also provided: P. (Pangaeus) docilis (Walker), P. (Pangaeus) moestus (Stal), Pangaeus (Homaloporus) punctilinea (Froeschner), and P. (Pangaeus) quinquespinosus (Froeschner). A list of the species of Pangaeus that have been recorded for Mexico is provided. A key to the Mexican species of Pangaeus is also given.